2014
DOI: 10.1002/polb.23591
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of free, restricted, and entrapped water environments in poly(N‐isopropyl acrylamide) hydrogels via1H HRMAS PFG NMRspectroscopy

Abstract: Different water environments in poly(N-isopropyl acrylamide) (PNIPAAm) hydrogels are identified and characterized using 1 H high resolution magic angle spinning (HRMAS) nuclear magnetic resonance (NMR). Local water environments corresponding to a "free" highly mobile species, along with waters showing restricted dynamics are resolved in these swollen hydro-gels. For photo-initiated polymerized PNIPAAm gels, an additional entrapped water species is observed. Spin-spin R 2 relaxation experiments support the argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 48 publications
0
20
1
Order By: Relevance
“…It has been reported that polymeric materials composed of identical monomer units but synthesized using different methods exhibit similar behavior, whereby different preparation methods produce distinct pore structures, and therefore different hydration environments between materials. 56 These differences in hydration environments can be characterized in terms of the binding strengths of water with the surface accessible facets of the pore structure, the diffusivity of water within the pores, and the extent to which water exchanges readily between the pore structure and the bulk fluid. Changes in these characteristics would suggest changes in the ease with which macromolecules, such as cellulases, diffuse from the bulk solution to the interior pores of the cellulose, explaining differences in reactivity between dried and neverdried cellulose materials, and these changes can be probed using 1 H HR/MAS NMR.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that polymeric materials composed of identical monomer units but synthesized using different methods exhibit similar behavior, whereby different preparation methods produce distinct pore structures, and therefore different hydration environments between materials. 56 These differences in hydration environments can be characterized in terms of the binding strengths of water with the surface accessible facets of the pore structure, the diffusivity of water within the pores, and the extent to which water exchanges readily between the pore structure and the bulk fluid. Changes in these characteristics would suggest changes in the ease with which macromolecules, such as cellulases, diffuse from the bulk solution to the interior pores of the cellulose, explaining differences in reactivity between dried and neverdried cellulose materials, and these changes can be probed using 1 H HR/MAS NMR.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This behavior has been attributed to water becoming trapped in segregated hydration environments upon rapid changes in the pore structure of semicrystalline polymeric materials. 56 Accordingly, the minor feature at 8.9 ppm is assigned to a partially "collapsed" cellulose pore structure that forms upon drying. 1, entries 9 and 10).…”
Section: T H Imentioning
confidence: 99%
“…As mentioned above, polymer hydrogels consist of cross-linked polymer swelled in a huge amount of water. It should be mentioned, that a majority of water exists in a 'free water' state in swollen hydrogels, and only a little fraction of water is in a bound state [18,19]. The presence of 'free water' in pores of hydrogels is an important condition that provides an aqueous medium, necessary for many types of ion-exchange reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions of water with antifreezing polymers also play a vital role in inhibiting the growth of ice crystals . On the other hand, hydrophobic hydration in polymers with nonpolar alkyl groups is equally important . In off‐shore gas drilling industry, a small amount of amphiphilic polymers added into the pipelines can kinetically inhibit the gas hydrate formation and prevent the pipelines from plugging during production .…”
Section: Introductionmentioning
confidence: 99%